The Portrayal and The Effects of Hyper-reality in Ready Player One Movie By Steven Spielberg (The Application of Jean Baudrillard’s Theory) - Sarniyati Dalimu; Ansor Putra; Rahmawati Azi (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2020)
Technology can create a hyperreality, hyperreality is an artificial reality that feels real. The portrayal of hyperreality is illustrated in one of the science-fiction movies named Ready Player One by Steven Spielberg. This study aims to analyze the portrayal and the effect of hyperreality that occurs in the society of Columbus, Ohio in Ready Player One movie. Based on the objective of this study, the writer uses Jean Baudrillard’s theory of hyperreality. In this study, the writer used a descriptive qualitative method to analyze and explain how hyperreality portrayed and affected the society of Columbus, Ohio in Ready Player One movie. The writer finds out that hyperreality is formed and portrayed through the simulation of technology. James Halliday is the famous expert and developer of games in Ohio who created a virtual world named the Oasis. People in Ohio use virtual reality as a tool to connect the Oasis and the real world. People spend their time in the Oasis because they can get freedom, money, and pleasure at the Oasis. it makes them rarely socialize in the real world. They also do not have jobs in the real world. Those are the effects of hyperreality that happened in Ready Player One movie by Steven Spielberg.